Pengembangan Ekowisata Mangrove Belagaone Karya sebagai Daya Tarik Wisata di Kabupaten Nunukan - Evalinda; Fareis Althalets (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2022)
Belagaone Karya Mangrove Ecotourism is one of the first mangrove tours built on the island of Nunukan. It has very good potential to attract visitors because apart from being an educational tour, it can also be a sport tourism for people who want to walk in the mangrove forest area. The purpose of this research on mangrove ecotourism is to find out how the development carried out on the Belagaoen Mangrove ecotourism This work, with research focused on Sustainable Tourism Development and analyzed using qualitative descriptive methods where the data in this study were obtained through observation, documentation and interviews with key informants. is the coach of the Nusa Karya Pokdarwis and the informant who is the Chair of the Nusa Karya Pokdarwis which manages the mangrove ecotourism of Belagaone Karya. From this study, it was found that the development of the Belagaone Karya mangrove ecotourism had been carried out quite well because every aspect of the development carried out was in accordance with the provisions and criteria of Sustainable Tourism Development in terms of ecology, culture and economy. It's just that it has several obstacles in the system of further development, where this development is quite influential in supporting the realization of the principles of sustainable tourism development from an economic and socio-cultural perspective. This is also due to limited funds and the Pokdarwis which until now has not formed a special management body to determine and regulate the fees for tourist attraction fees.